Chitosan-derived hydrothermally carbonized materials and its applications: A review of recent literature - Hani Ababneh (9218272) (2021)
Chitosan (CS) is a linear polysaccharide biopolymer, one of the most abundant biowastes in the environment. This makes chitosan a potential material for a wide range of applications. To improve CS's properties, chitosan has to be chemically modified. Hydrothermal carbonization (HTC) is a sustainable process for converting chitosan to solid carbonized material. This article presents a review on the applications of hydrothermally treated chitosan in different fields such as water treatment, heavy metals adsorption, carbon dioxide capturing, solar cells, energy storage, biosensing, supercapacitors, and catalysis. Moreover, this review covers the impact of HTC process parameters on the properties of the produced carbon material. The diversity of applications indicates the great possibilities and multifunctionality of hydrothermally carbonized chitosan and its derivatives. The utilization of HTC-CS is expected to further expand as a result of the movement toward sustainable, environmentally-friendly resources. Thus, this review also recommends a few suggestions to improve the properties of HTC chitosan and its comprehensive applications. Other Information Published in: International Journal of Biological Macromolecules License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijbiomac.2021.06.161